Attitudes of Vocational Education Students toward using the Internet to Achieve Academic Motivation for Self-Learning from their Point of View - Al-Momani, Mohammad Omar (Journal of Ecohumanism, 2024)
The study aimed to identify the attitudes of vocational education students towards using the Internet to achieve academic motivation for self-learning from their point of view and the relationship of this to some variables such as gender and the number of hours of daily use. The descriptive approach was used, in addition to the questionnaire, which consisted of (16) items as a tool for the study, It was applied to (150) male and female students majoring in vocational education at Al-Balqa Applied University in Jordan in the first semester of the academic year (2023/2024). The results showed that the attitudes of vocational education students toward using the Internet to achieve academic motivation for self-learning came at a high level, with a mean of (2.71) and a standard deviation of (0.60). The results also showed that there were statistically significant differences attributed to the gender variable and in favor of males. The results also indicated that there were no statistically significant differences between the estimates of the study sample due to the variable number of hours of use.